1993
DOI: 10.1128/aac.37.6.1270
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of 18F-labeled fluconazole in healthy human subjects by positron emission tomography

Abstract: The distribution of fluconazole in tissue of human volunteers was determined by positron emission tomographic scanning over a 2-h period following the infusion of a tracer dose of 18F-fluconazole (5 to 7 mCi) plus 400 mg of unlabeled drug (the standard daily dose of fluconazole). Previous studies have validated this approach for animals. From serial positron emission tomographic imaging and blood sampling, pharmacokinetics of fluconazole in tissue were determined. There was significant distribution of the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 30 publications
1
51
0
1
Order By: Relevance
“…The second technique refers to positron emission tomographic scanning used by Fischman et al [81] 18 F-labeled fluconazole was given to healthy volunteers and determined in the heart by PET. Its level there was almost twofold higher than in blood, indicating fluconazole efficacy in treating fungal infection of the heart, but also, from a pharmacokinetic point of view, drug accumulation in cardiac tissue [81].…”
Section: Antifungal and Anticancer Drugsmentioning
confidence: 99%
“…The second technique refers to positron emission tomographic scanning used by Fischman et al [81] 18 F-labeled fluconazole was given to healthy volunteers and determined in the heart by PET. Its level there was almost twofold higher than in blood, indicating fluconazole efficacy in treating fungal infection of the heart, but also, from a pharmacokinetic point of view, drug accumulation in cardiac tissue [81].…”
Section: Antifungal and Anticancer Drugsmentioning
confidence: 99%
“…Fluconazole is also readily detectable in human brain parenchyma. Studies with 18 F-fluconazole in volunteers showed brain tissue concentrations that were similar to those in plasma, with some minor regional variation (71). However, in five surgical patients, fluconazole brain tissue/plasma concentration ratios of 0.7 to 2.4 were measured when the fluconazole plasma concentrations were at 90% of steady-state values (72).…”
Section: Brain and Cerebrospinal Fluidmentioning
confidence: 99%
“…Therefore, we presumed that dermatophytes might also be resistant to fluconazole and were interested in the resistance mechanism of fluconazole in dermatophytes. Fischman et al reported that levels of fluconazole Ͼ10 g/g of human tissue were needed to treat infection with Cryptococcus neoformans, Coccidioides immitis, and Histoplasma capsulatum (5). This observation prompted us to adjust the concentration of fluconazole in the medium to 20 g/ml for our experiments on the effect of fluconazole and/or proteasome inhibitor on fungal growth.…”
Section: Discussionmentioning
confidence: 99%